Demographical properties of West Turkistan - KURT, HALİL (ELSEVIER SCIENCE BV, 2011)
After 1990, fifteen states gained their independence from the former Soviet Union. The Central Asian countries which include Uzbekistan, Kazakhstan, Kyrgyzstan, Turkmenistan and Tajikistan were among those states. These five countries cover an area of 4 million square kilometer and have a population of 60 million. The population of West Turkistan was 49.4 million according to the last census statistics during the former Soviet Union period in 1989. This number has risen up to 59.3 million according the latest census in 2005. During the same period, the population of Russian federation decreased from 147 million to 143.4 million and the population in Ukraine declined from 51.7 million to 47.4 million. In the last fifteen years not only the population increased but also the demography changed in West Turkistan. While the population rate of Turks and Muslim ethnic minorities increased the Orthodox Christians and Slavic (Russian, Ukrainian etc.) population rate has decreased. The main cause is the birth rate and the migrations to Russian federation. In this study, these five countries in West Turkistan have been investigated in details in terms of population, population density, age and gender properties, birth rate, population growth rate, rural and urban population, migrations, language, religion and ethnic structures in population growth effect between the years 1989-2005. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The 2nd International Geography Symposium-Mediterranean Environment
Keywords: demography; west turkistan; independence; population